Muscle fatigue is attenuated when applying intermittent compared with continuous blood flow restriction during endurance cycling - Corvino, R. B.; da Luz Scheffer, D.; Penteado dos Santos, R.; Latini, A.; Oliveira, A. S.; Caputo, F. (International Journal of Sports Physiology and Performance, 2022)
Purpose: The aim of this study was to identify a blood-flow-restriction (BFR) endurance exercise protocol that maximizes metabolic strain and minimizes muscle fatigue. Methods: Twelve healthy participants accomplished 5 different interval cycling endurance exercises (2-min work, 1-min rest) in a randomized order: (1) control, low intensity with unrestricted blood flow (CON30); (2) low intensity with intermittent BFR (i-BFR30, ~150 mm Hg); (3) low intensity with continuous BFR (c-BFR, ~100 mm Hg); (4) unloaded cycling with i-BFR0 (~150 mm Hg); and (5) high intensity (HI) with unrestricted blood flow. Force production, creatine kinase activity, antioxidant markers, blood pH, and potassium (K+) were measured in a range of 5 minutes before and after each cycling exercise protocol. Results: HI showed the highest reduction (delta = -0.26 [0.05], d = 5.6) on blood pH. Delta pH for c-BRF30 (delta = -0.02 [0.03], d = 0.8) and delta pH for i-BRF30 (delta = -0.04 [0.03], d = 1.6) were different from each other, and both were higher compared with CON30 (delta = 0.03 [0.03]). There was significant before-to-after force loss following HI (delta = 55 [40] N·m-1, d = 1.5) and c-BFR30 (delta = 27 [21] N·m-1, d = 0.7) protocols only, which were accompanied by significant increases in K+ (HI: delta = 0.94 [0.65] mmol·L-1, d = 1.8; c-BFR30: delta = 0.72 [0.85] mmol·L-1, d = 1.2). Moreover, all BFR conditions elicited slight increases in plasma creatine kinase, but not for HI and CON30. Glutathione changes from before to after were significant for all BFR conditions and HI, but not for CON30. Conclusions: The attenuation in fatigue-induced reductions in maximal force suggests that i-BFR exercise could be preferable to c-BFR in improving exercise capacity, with considerably less biologic stress elicited from HI exercises.